Switzerland : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the economy of Switzerland withstood relatively well the sharp appreciation that followed the exit from the exchange rate floor. Economic performance has continued to firm in 2016 with support from domestic and external demand. GDP growth is forecast to reach 1.5 percent in 2016, and to stabilize at 1.7 percent over the medium term. Inflation is expected to return to positive territory in 2017 and to continue to rise to the middle of the target band. However, important external and domestic risks could affect this outlook, including resurgence in global financial market volatility, renewed concerns about the financial health of large global banks, and changes in Swiss-European Union economic relations.